2021
DOI: 10.1001/jamacardio.2021.0683
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Disparities in Cardiovascular Health Care Among Patients With Premature Atherosclerotic Cardiovascular Disease

Abstract: IMPORTANCEThere is a paucity of data regarding secondary prevention care disparities in women with premature and extremely premature atherosclerotic cardiovascular disease (ASCVD), defined as an ASCVD event at 55 years or younger and 40 years or younger, respectively.OBJECTIVE To evaluate sex-based differences in antiplatelet agents, any statin, high-intensity statin (HIS) therapy, and statin adherence in patients with premature and extremely premature ASCVD. DESIGN, SETTING, AND PARTICIPANTSThis was a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…In adjusted analyses, females were less likely to receive antiplatelet therapy (OR, 0.47 [95% CI, 0.45–0.50]), any statin (OR, 0.62 [95% CI, 0.59–0.66]), or high-intensity statin (OR, 0.63 [95% CI, 0.59–0.66]) than males. 114…”
Section: Coronary Heart Disease Acute Coronary Syndrome and Angina Pe...mentioning
confidence: 99%
“…In adjusted analyses, females were less likely to receive antiplatelet therapy (OR, 0.47 [95% CI, 0.45–0.50]), any statin (OR, 0.62 [95% CI, 0.59–0.66]), or high-intensity statin (OR, 0.63 [95% CI, 0.59–0.66]) than males. 114…”
Section: Coronary Heart Disease Acute Coronary Syndrome and Angina Pe...mentioning
confidence: 99%
“…However, in a study of veteran patients with PAD, young women were also less likely to receive antiplatelet therapy than men (59% versus 78%, respectively). 185 These findings support the need for further investigation into differential use by sex of this important class of therapies proven to reduce risk of atherothrombotic events in PAD.…”
Section: Antithrombotic Therapymentioning
confidence: 52%
“…A recent VA study found similar gender-based disparities in the use of antiplatelet medications and statins among women with premature atherosclerotic CVD compared to men. 16 Our study underscores the critical need to understand reasons for the relative undertreatment of women with guideline-concordant care.…”
Section: Discussionmentioning
confidence: 78%
“…15 Although prior research has examined risk factors, only one study has examined possible disparities by gender in established CVD. 16 Furthermore, no research has examined if there are gender differences in medical therapy for HF among Veterans. Given the increasing burden of CVD in women Veterans and limited data on guideline-directed medical therapy (GDMT) in this high-risk population, we sought to determine if there are gender differences in the provision of outpatient GDMT for CAD and HF.…”
Section: Introductionmentioning
confidence: 99%